THE INCIDENCE OF THE PANDEMIC CONTEXT ON THE SOCIAL EXCLUSION AND MATERIAL DEPRIVATION IN ROMANIA - Mandalac, Antonia; Iatagan, Mariana (Annals of Spiru Haret University. Economic Series, 2023)
In Romania, social exclusion highlights a reality that removes the perspectives of sustainable development of social equity and economic stability. The pandemic context caused a major discrepancy between national socio-economic environments, placing Romania first in the European ranking regarding the level of social exclusion and material deprivation. The insufficient space of the labor market, the intensity of unemployment, the government restrictions imposed to limit the pandemic context argue the alarming statistics of social exclusion, while the policies and strategies implemented to ensure an honorable standard of living for the Romanian population do not show notable results, limiting the possibilities reducing the level of poverty. The purpose of the article is to measure the level of social exclusion and material deprivation in Romania, formulating sustainable proposals for improving the quality of life of people whose socio-economic status is at the limit of existence.